List w służbie pamięci. Dokumentalny wymiar korespondencji Wisławy Szymborskiej i Kornela Filipowicza - Wojciechowska, Anna (Stylistyka, 2019)
The paper focuses on the documentary aspect of a letter as a speech genre. The corpus comprises the letters exchanged between Wisława Szymborska and Kornel Filipowicz, written between 1966 and 1985. The study aims toanalyse how the participants of the epistolary dialogue present historic and social issues, and to what extent a private letter may serve memory. The analysis proves that the topics in the texts revolve around every day and ordinary issues – important only for the correspondents. Historical facts and social affairs are reported selectively, always from the sender’s point of view, and in relation to the addressee and the circumstances. They are often expressed in a disguised form (by means of allusion, understatement, joke, irony) which is determined by two factors: the fear of censorship and the correspondents’ literary abilities and their similar personality traits. The data reveals that a letter – considered as one’s account of events and a secondary mnemonic genre – may serve memory onlyin some ways but not completely because it “remembers” the past in a relative and limited way.